2015
DOI: 10.1007/s11205-015-1136-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Induced Abortion and Foreign Irregular Presence Using the Randomized Response Crossed Model

Abstract: We present the theoretical framework and the results of a pilot survey conducted in Calabria, a region in the south of Italy, to investigate the prevalence of two sensitive characteristics, namely induced abortion among foreign women residing in this region, and irregular immigrant status. Collecting data on these two attributes by means of traditional survey modes typically produces underestimates of the diffusion of the phenomena due to the stigmatizing nature of the investigated topics. In order to overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Tourangeau and Yan (2007) suggested that misreporting about sensitive topics is common and largely situational, its extent depending on whether the respondent has anything embarrassing to report, and on the design features of the survey. The RRT is designed to decrease social desirability bias and thus obtain more reliable estimates (Arnab & Singh, 2010; De Jong et al, 2012; Geng et al, 2016; Krebs et al, 2011; Lara et al, 2006; Miner, 2008; Oliveras & Letamo, 2010; Perri et al, 2015; Shamsipour et al, 2014; Simon et al, 2006; Striegel et al, 2010). Our results are consistent with those obtained by De Jong et al (2012), who compared nonstudent samples from two countries on permissive sexual attitudes and risky sexual behavior, using a RRT, and highlighted the advantages of using RRT in sensitive issues like sexual behavior, where it can be very difficult to obtain accurate responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tourangeau and Yan (2007) suggested that misreporting about sensitive topics is common and largely situational, its extent depending on whether the respondent has anything embarrassing to report, and on the design features of the survey. The RRT is designed to decrease social desirability bias and thus obtain more reliable estimates (Arnab & Singh, 2010; De Jong et al, 2012; Geng et al, 2016; Krebs et al, 2011; Lara et al, 2006; Miner, 2008; Oliveras & Letamo, 2010; Perri et al, 2015; Shamsipour et al, 2014; Simon et al, 2006; Striegel et al, 2010). Our results are consistent with those obtained by De Jong et al (2012), who compared nonstudent samples from two countries on permissive sexual attitudes and risky sexual behavior, using a RRT, and highlighted the advantages of using RRT in sensitive issues like sexual behavior, where it can be very difficult to obtain accurate responses.…”
Section: Discussionmentioning
confidence: 99%
“…Warner’s study generated a large body of research literature on alternative RRTs for eliciting sensitive information (Arnab, 2002, 2004; Bouza, 2009; Clark & Desharnais, 1998; Diana & Perri, 2010, 2012; Santiago, Bouza, & Al-Omari, 2016; Singh & Sedory, 2011; Ulrich, Schröter, Striegel, & Simon, 2012) in studies of socially undesirable behavior. The potential generalization of the technique to other cultures has been demonstrated by studies related to China (Geng, Gao, Ruan, Yu, & Zhou, 2016), Iran (Vakilian, Mousavi, & Keramat, 2014), the United States (Walsh & Braithwaite, 2008), Europe (Perri, Pelle, & Stranges, 2015), and Spain (Cobo, Rueda, & López-Torrecillas, 2017), all of which observe that surveys based on indirect questioning are commonly used when the questions relate to sensitive issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Arnab and Singh (2010) demonstrated how RRT could be used in the Botswana AIDS Impact Survey. Ostapczuk et al (2009) studied attitudes toward foreigners, whereas Perri et al (2016) dealt with induced abortion and migrants’ irregular presence. Hsieh et al (2010) considered the proportion of illegal cable TV in Taiwan, and Tu and Hsieh (2017) studied extradyadic sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent contributions, although not exhaustive, cover a great variety of topics. For instance: the measure of the impact of HIV/AIDS infection in Botswana (Arnab & Singh, ); the assessment of sensitive health‐risk behaviors in HIV/AIDS positive individuals (Arentoft et al., ); the assessment of permissive sexual attitudes and high‐risk sexual behaviors to reduce the transmission and acquisition of sexually transmitted infections and HIV/AIDS (De Jong, Pieters, & Stremersch, ; Starosta & Earleywine, ; Geng, Gao, Ruan, Yu, & Zhou, ; Kazemzadeh, Shokoohi, Baneshi, & Haghdoost, ); patterns of condom use among university students for HIV/AIDS control programs (Safiri, ; Vakilian, Mousavi, Keramat, & Chaman, ); the prevalence of sexual behaviors such as extradyadic sex (Tu & Hsieh, ), commercial sex among homosexual men (Chen et al., ) and sexual assault (Krebs et al., ); the use of drug, and athletic, cognitive, and mood performance‐enhancing substances (Striegel, Ulrich, & Simon, ; Petróczi et al., ; Dietz et al., 2013; Franke et al., ; James, Nepusz, Naughton, & Petróczi, ; Nakhaee, Pakravan, & Nakhaee, ; Stubbe, Chorus, Frank, de Hon, & van der Heijden, ; Shamsipour et al., ; Khosravi et al., ; Cobo, Rueda, & López‐Torrecillas, ); smoking behavior validation studies (Fox, Avetisyan, & van der Palen, ); dental hygiene habits of Chinese college students (Moshagen, Musch, Ostapczuk, & Zhao, ); farmers' transgressionary behaviors and prevalence of animal diseases such as sheep scab in Wales (Cross, Edwards‐Jones, Omed, & Williams ), African swine fever in Madagascar (Randrianantoandro, Kono, & Kubota, ), or foot and mouth disease‐infected animals in Sri Lanka (Gunarathne, Kubota, Kumarawadu, Karunagoda, & Kon, ); estimation of the prevalence of induced abortion (Oliveras & Letamo, ; Moseson et al., ; Perri, Pelle, & Stranges, ); ecological and biological conservation issues including estimation of illegal bushmeat hunting (Nuno, Bunnefeld, Naiman, & Milner‐Gulland, ; Conteh, Gavin, & Solomon, ), illegal fishing (Blank & Gavin, ; Arias & Sutton, ), and unauthorized natural resources use (Harrison, Baker, Twinamatsiko, & Milner‐Gulland, ).…”
Section: Introductionmentioning
confidence: 99%